A Study on the Attachment Effect of CFRP Plates to Internal Reinforcements of Curtain Wall Frames Using GFRP - Lee, Yong-Taeg; Kim, Seung-Hun; Park, Hae-Yong; Choi, Jin-Chul; Park, Se-Hee (International Journal of Membrane Science and Technology, 2023)
This study is for the development of internal reinforcing materials using fiber-reinforced plastics that can be used for curtain wall frames. The main material of the reinforcement is light and inexpensive GFRP. However, GFRP has characteristics of low elastic modulus and brittle fracture. Therefore, CFRP is attached to supplement the disadvantages. In this study, a flexural experiment was performed to confirm the performance improvement effect of GFRP reinforced with CFRP. The results of the flexural experiment showed that the total flexural stiffness increased by about two times when the carbon fiber reinforced plastic plate was attached compared to the specimen made of a single material of glass fiber reinforced plastic. Also, the pattern of the load-displacement graph was found to reflect the characteristics of the ductile material. However, it was observed that adhesion failure first occurred on the attachment surface before the member yielded. Therefore, it was determined that it was necessary to increase the adhesive strength or set the minimum length in order to prevent poor adhesion when manufacturing actual stiffeners. Therefore, in this study, additional specimens were prepared using the specimen length, adhesive strength, and adhesive rate as variables, and then the experiment was conducted. As a result of the experiment, the maximum load decreased in the long specimen, but the overall stiffness was similar, and adhesive failure did not appear conspicuously before the member was destroyed. In the case of adhesive strength, the case using epoxy was more stable than the specimen using resin, and the maximum load and stiffness were slightly higher when the adhesive width of carbon fiber reinforced plastic was the whole.